Estimation of Repeatability and Most Probable Producing Ability (MPPA) of Sapudi Sheep Based on Daily Body Weight Gain of Lambs from Birth to Pre-weaning and Weaning - Mudawamah Mudawamah; M. Z. Anwar; Sumartono Sumartono (Universitas Bengkulu, 2022)
This research aimed to estimate the repeatability and MPPA values of Sapudi ewes based on the lamb’s daily gain from birth to pre-weaning and weaning. Using recorded data in a pedigree of lamb, 53 data with half-sib relationship came from 14 ewes which included the record of body weight gain of Sapudi lambs from birth to pre-weaning and weaning. The data were analyzed by descriptive method with a quantitative approach. The study showed that the average daily gain of pre-weaning and weaning was 007 kg/day. The repeatability value of pre-weaning and weaning daily gain was 0.636 in the high category and 0.377 in the medium category. The MPPA daily gain values for pre-weaning and weaning ranged from -0.032 to 0.018 and -0.016 to 0.009. The research concluded that the Sapudi sheep ewes based on the MPPA daily gain pre-weaning were six heads with four rankings, while the daily weight gain weaning was ten heads with ranking of five. The highest rank of Sapudi ewes in pre-weaning and weaning daily gain was ear tag 094 with MPPA values of 0.018 and 0.009. It is recommended that further research can be conducted to estimate the repeatability value of quantitative periodically as the basis for the selection and culling of livestock.